Perbedaan Hasil Belajar Kognitif Siswa Berdasarkan Gender Melalui Penerapan Model Pembelajaran Kooperatif Berbasis Kolaboratif Sainstifik - Syafaruddin, Syafaruddin; Dewi, Ika Nurani; Utami, Septiana Dwi (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2022)
The purpose of this study was to describe students' cognitive learning outcomes based on gender differences through the application of a scientific collaborative-based cooperative learning model at SMP Darul Hikmah Mataram. This research is a pre-experimental research with a one-shot case study design. The instrument used in this study was a cognitive learning outcome test. Further processed using quantitative descriptive analysis techniques. The results showed that the average cognitive learning outcomes of students was 66.74. Based on gender, the learning outcomes of male students were 49.1, while female students were 50.4. This shows that the cognitive learning outcomes of female students are higher than that of male students through the application of a scientific collaborative-based cooperative learning model.